Managing the Menopause through 'Abjection Work': When Boobs Can Become Embarrassingly Useful, Again. (August 2020) - Butler, Clare
This article examines how power and menopause relate at work. Based on qualitative data from 23 women administrative workers, the research finds that menopausal symptoms are sometimes 'awful', 'knackering' and 'isolating'. Yet, as 'real' or 'normal women', they described getting lost in the menopause discourse and many spoke of going through 'the change' instead; this saw them make sense of, and respond to, their symptoms in (sometimes) unconventional ways. In addition, when a menopausal body runs rampant, its abject appearance can cause embarrassment, but not just for the woman – for anyone who witnesses it. For some women, they simply go and stand outside. For others, the realisation of the vicarious nature of embarrassment sees them employ their menopausal bodies and do 'abjection work'. This work acts as a powerful form of management; yet some might argue that it is improper.